HUBUNGAN ANTARA ADVERSITY QUOTIENT (AQ) DENGAN PRESTASI BELAJAR MAHASISWA ANGKATAN 2012 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Kurnia, Delta Kurnia; ", Firdaus; ", Zulharman (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The success of learning can be evaluated of learning achievement that has been achieved. Learning achievement is influenced by several factors, one of which is adversity quotient. Someone who has adversity quotient in any circumstances be able to use all its potential to improve learning achievement results. The purpose of study was to determine the correlation of Adversity Quotient (AQ) and academic achievement in year 2012 Medical Student of Riau University. This research used analytic method of cross sectional study. The population was students Faculty of Medicine University of Riau in year 2012. Sample of this research was 115 students with total sampling method. Researcher used a questionnaire based on the theory of Stoltz’s adversity quotient and Grade Point Average (GPA) to measure learning achievement. The statistical test for correlation of adversity quotient and learning achievement using Pearson correlation test. The result of this study showed a significant correlation between adversity quotient and learning achievement (r=0,377; p=0,000). In conclusion there was a correlation between Adversity Quotient (AQ) and learning achievement in year 2012 Faculty of Medicine University of Riau.Keywords: adversity quotient, learning achievement, medical student